Using stable isotope ratio to differentiate the Tunisian indigenous lamb grazing two different pasture types - Mekki I.; Smeti S.; Yagoubi Y.; Hajji H; Camin F.; Perini M.; Mahouachi M.; Piasentier E.; Atti N. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The efficacy of isotope ratio mass spectrometry (IRMS) in tracing lamb production systems was investigated for four farming systems in the Tunisian North-West: Ain Draham and Fernana, characterized by woody pasture, and Amdoun and Joumine, characterized by herbaceous pasture. Mixed breed lambs aged 3.5–5 months were reared under semi-extensive and extensive systems. Samples of Longissimus dorsi muscle were taken from eight lambs for each farming system for stable IR assessment of the three main bio-elements (C, N, S) in the protein and fat fractions of lamb. Using partial least squares discriminate analysis (PLSDA) the IR profiles of Tunisian lamb types allowed correct assignment of the training meat samples to pasture type. A broader scale pasture type discriminating lambs from the Amdoun (herbaceous pasture), the rest of north-west Tunisia appeared to be workable.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)